KERENTANAN BANJIR DI KECAMATAN MARTAPURA BARAT KABUPATEN BANJAR - Juwita Risanty; Deasy Arisanty; Eva Alviawati (JPG (Jurnal Pendidikan Geografi), 2015)
The study, titled Vulnerability to flooding in West Martapura of Banjar Regency research objectives the purpose of this research is to know the level of vulnerability to flooding in the Western County of Martapura of Banjar.The population in this research is a community located in the Sub-district Martapura Barat in 13 villages in the Sub-District Martapura Barat with sample taken randomly from 13 villages in the Sub-District Martapura Barat, each of which was taken on the basis of every family in the village of yangmewakili the population so that the total number of samples is 333 respondents using Random Sampling techniques. Primary data obtained through observation, measurement and direct question form technique in field, secondary data were obtained from the Office of Sub-district Martapura Barat, Regional disaster response Agency (BPBD), Banjar Regency, and regional development planning Board (BAPPEDA) Banjar Regency and the Central Bureau of statistics (BPS) Banjar Regency. Analysis techniques used by using analysis of percentage.The results showed that Vulnerability to flooding in Martapura barat i.e. much influence by the social economic and environmental factors.Key Words: vulnerability, Flood, Community.